Ab initio calculation of the intermolecular potential and prediction of second virial coefficients for dimer H2-H2 - Tat, Pham Van; Deiters, U. K. (Vietnam Journal of Chemistry, 2014)
The intermolecular pair potentials of the dimer H2-H2 were constructed from quantum mechanics using method CCSD(T) with Dunning's correlation-consistent basis sets aug-cc-pVmZ (m = 2, 3, 4); ab initio energies were extrapolated to the complete basis set limit. The interaction energies were corrected for the basis set superposition error (BSSE) with the counterpoise scheme. The second virial coefficients of hydrogen resulting from ab initio potential functions were obtained by integration; corrections for quantum effects were included too. The results agree well with experimental data.Keywords: ab initio potential, dimer H2-H2, second virial coefficients, BSSE.